2006
DOI: 10.1080/10601320600896645
|View full text |Cite
|
Sign up to set email alerts
|

Poly(acrylate‐b‐styrene‐b‐isobutylene‐b‐styrene‐b‐acrylate) Block Copolymers via Carbocationic and Atom Transfer Radical Polymerizations

Abstract: A series of polyacrylate-polystyrene-polyisobutylene-polystyrene-polyacrylate (X-PS-PIB-PS-X) pentablock terpolymers (X ¼ poly(methyl acrylate) (PMA), poly(butyl acrylate) (PBA), or poly(methyl methacrylate) (PMMA)) was prepared from poly (styrene-b-isobutylene-b-styrene) (PS-PIB-PS) block copolymers (BCPs) using either a Cu(I)Cl/1,1,4,7,7-pentamethyldiethylenetriamine (PMDETA) or Cu(I)Cl/tris[2-(dimethylamino)ethyl]amine (Me 6 TREN) catalyst system. The PS-PIB-PS BCPs were prepared by quasiliving carbocationi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Relatively few investigations of symmetric ABCBA pentablock terpolymers have appeared in the literature. ,, Previous reports have focused on synthetic methodology, , hydrogel , or ion gel formation, and micellization in solvents. ,,, Only a few reports have interrogated ABCBA pentablock terpolymers in the bulk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few investigations of symmetric ABCBA pentablock terpolymers have appeared in the literature. ,, Previous reports have focused on synthetic methodology, , hydrogel , or ion gel formation, and micellization in solvents. ,,, Only a few reports have interrogated ABCBA pentablock terpolymers in the bulk.…”
Section: Discussionmentioning
confidence: 99%
“…Heating ISO-7a to 250 °C decreased the segregation strength and increased the chain mobility, enabling the sample to adopt Relatively few investigations of symmetric ABCBA pentablock terpolymers have appeared in the literature. 45,62,[64][65][66][67][68][69][70][71][72][73][74][75][76] Previous reports have focused on synthetic methodology, [64][65][66][67]69 hydrogel 72,76 or ion gel 75 formation, and micellization in solvents. 62,68,70,71 Only a few reports have interrogated ABCBA pentablock terpolymers in the bulk.…”
Section: Discussionmentioning
confidence: 99%
“…Difunctional PIB, capped with several units of styrene, Cl-St- b -PIB- b -St-Cl, prepared cationically was used as an efficient difunctional macroinitiator for homogeneous ATRP. It was extended via ATRP with well-defined segments built from styrene (St), methyl acrylate (MA), methyl methacrylate (MMA), and isobornyl acrylate (IBA). Recently, Faust et al reported a straightforward synthesis of PIB terminated with an allyl halide group (PIB-allyl-X, where X = Br or Cl) using cationic polymerization. , It was achieved by the addition of 1,3-butadiene (BD) in the presence of Me 1.5 AlBr 1.5 or TiCl 4 co-initiator to living PIB.…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of ATRP has opened a new route for the controlled synthesis of several block copolymers (4,5). A wide variety of block copolymers can be derived from the same family of vinyl monomers (6,7) or different families of vinyl monomers via ATRP (8).…”
Section: Introductionmentioning
confidence: 99%